Metabolic modulation of yogurt fermentation kinetics and acidification by Bifidobacterium-starter culture interactions - Zhao, Zhi; Shi, Shaoqi; Zhang, Lele; An, Meilun; Wen, Pengcheng; Sang, Yue; Feng, Haihong; Hou, Baochao; He, Jian; Hung, Wei-Lian; Li, Baolei; Zhao, Liang; et al. (Frontiers in Microbiology, 2026)
IntroductionProbiotic-fortified yogurt has gained substantial consumer preference owing to its well-documented health benefits. However, stability of probiotic yogurt necessitates a comprehensive understanding of microbial dynamics throughout fermentation and storage.MethodsThis study employed an integrated approach combining fermentation kinetics, post-acidification profiling, and untargeted metabolomics to explore the complex interactions between three Bifidobacterium strains (B. animalis 23426, B. bifidum 91, and B. longum BB68S) and starter cultures (HYY) during symbiotic fermentation.ResultsThe results demonstrate that Bifidobacterium supplementation notably enhanced the biomass of S. thermophilus (8.13–8.54 lg CFU/mL) after 2 h by upregulating galactose catabolism and riboflavin biosynthesis, thereby reducing fermentation time by 0.5 to 2 h. In contrast, competitive exclusion effects caused a decrease in L. bulgaricus biomass by 0.2 to 0.8 log CFU/mL. Over 21-day of refrigerated storage, the acid accumulation in Bifidobacterium-enriched yogurts was significantly lower (Δ 3.08–7.49 °T) than in HYY yogurt (Δ 9.42 °T), primarily by downregulation key metabolic pathways involving glycerophospholipid metabolism, branched-chain and aromatic amino acid metabolism, and cofactor biosynthesis, leading to reduced post-acidification.DiscussionTherefore, Bifidobacterium accelerates fermentation by promoting S. thermophilus biomass while mitigating post-acidification by inhibiting L. bulgaricus. The results provide a scientific basis for developing next-generation probiotic yogurts with controlled acidification profiles and improved shelf-life characteristics.